Amperometric Trace Determination of Cu(II), Ag(I), Au(III), Pd(II) and Pt(IV) with 2-Mercapto and 3-Mercaptoprpanoic acids - Agrawal, O.P.; Verma, K.K.; Khatkar, S.P.; Kumar Malik, Rajesh (Asian Journal of Chemistry, 2010)
Amperometric determination of trace amounts of Cu(II), Ag(I), Au(III), Pd(II) and Pt(IV) is reported with the help of 2-mercaptopropanoic acid (RSH) and 3-mercaptopropanoic acid (MPSH) at d.m.e. Lowest determinable concentration ranges from 3 ppm to 20 ppm depending upon the metal ion. The fundamental reaction involved in all the cases is complexation. M:L ratio is 1 : 1 for Cu(II), Au(III), Pd(II) and Pt(IV) when any of the ligands is employed as titrant; this ratio for Cu(II), however, changes to 1 : 2 if the ligand is MPSH. If the metal ion is used as titrant, the M : L ratio is 1:2 in case of Cu(II), Au(III) and Pd(II) and 1 : 1 in case of Ag(I). Tolerance for diverse foreign ions has been worked out.